THE RELATIONSHIP BETWEEN LANGUAGE AND SOCIETY - Muhammadjonova Madina Nozimjon qizi; Z.A. Umirova (Ta’lim innovatsiyasi va integratsiyasi, 2025)
ABSTRACT This article investigates the complex and multifaceted relationship between language and society, emphasizing the ways in which language both shapes and reflects social identities, cultural values, and power structures. It explores key sociolinguistic concepts, including language variation, identity, and linguistic inequality, demonstrating the crucial role that language plays in constructing and maintaining social realities. By examining the processes of language change and highlighting the importance of preserving linguistic diversity, the article argues for the dynamic and essential nature of language as a foundational element of human society, deeply intertwined with the social, cultural, and political fabric of communities. Through this lens, the article aims to shed light on the ongoing transformations in language use and the significant impact these shifts have on the construction of identity, societal norms, and power relations. By analyzing language change and the importance of preserving linguistic diversity, the article emphasizes language as a dynamic and essential element of human society 1 .